WEBSITE-BASED LOAN APPLICATION INFORMATION SYSTEM AT PT. BPR BKK JATENG BANYUMAS - Inayah Nur, Hanifah; Yosita, Lianawati; Monika Gisthi, Secaresmi; Adhi, Wibowo; Suyudi, Suyudi (LPPM STMIK Dharmapala Riau, 2024)
PT. BPR BKK Jateng, Banyumas Branch is a financial institution whose main activity is savings, but in addition to savings, it also serves credit loan and deposit applications. In the credit loan application system that is currently running at PT. BPR BKK Jateng, Banyumas Branch, where customers who want to apply for a credit loan still have to come directly to the bank. This is considered ineffective, because it makes customers have to come directly to the bank many times when there are incomplete credit application requirements. A website-based credit loan application information system needs to be created to facilitate the credit loan application process. A website-based information system was chosen because of its advantage, namely that it can be accessed anywhere using an internet connection. The method used in creating this website-based credit loan application system uses the SDLC (System Development Life Cycle) method with a waterfall model. This system is built using the programming language PHP (Hypertext Preprocessor), CodeIgniter Framework, MySQL Database. The result of this final assignment is a system that can help customers more easily apply for credit loans, access information about credit loan services and help admins more easily document credit loan application data at PT. BPR BKK Jateng, Banyumas Branch.